2019
DOI: 10.1002/ajmg.a.61446
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant inheritance in a recently described ZMIZ1‐related neurodevelopmental disorder: Case report of siblings and an affected parent

Abstract: ZMIZ1, zinc finger MIZ‐domain containing 1, has recently been described in association with syndromic intellectual disability in which the primary phenotypic features include intellectual disability/developmental delay, seizures, hearing loss, behavioral issues, failure to thrive, and various congenital malformations. Most reported cases have been found to result from de novo mutations except for one set of three siblings in which parental testing could not be performed. With informed consent from the family, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…To date, 15 pathogenic, or likely pathogenic, ZMIZ1 variants have been described in 18 families, most of which represent de novo events. Two families were reported with dominantly inherited mutations and intra-familial variability [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 15 pathogenic, or likely pathogenic, ZMIZ1 variants have been described in 18 families, most of which represent de novo events. Two families were reported with dominantly inherited mutations and intra-familial variability [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Given clinical similarities of the phenotypes, caused by biallelic mutations of OTUD6B and heterozygous ZMIZ1 mutations, and that the present patient harbored genetic defects of these two genes, we compared the phenotypes of the present patient to those in previous reports, as summarized in Table 1 [5][6][7][8][9][10][11][12].…”
Section: Clinical Similarities and Differences Comparing Between Otud6b-and Zmiz1-related Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven distinct regions were identified, one alanine-rich region (aa280-305, E-score = 2.1E-06), two proline-rich regions (aa334-555, E-score = 3.9E-16; aa867-1002, E-score = 3.8E-07), one bipartite nuclear localization signal (NLS, aa697-711, E-score = 2.1E+04), MIZ/SP-RING zinc finger (aa738-787, E-score = 1.1E-33), and one copper binding octapeptide (aa947-954, E-value = 1.5). All variants of ZMIZ1 were also recruited from the DECIPHER database ( Swaminathan et al, 2012 ) and the four published articles ( Córdova-Fletes et al, 2015 ; Carapito et al, 2019 ; Latchman et al, 2020 ; Phetthong et al, 2021 ). A total of 33 patients with ZMIZ1 pathogenic variants were collected, 1 from our current cohort ( Figures 4A,B ), 8 from the DECIPHER database ( Figure 4C ), and 24 from published articles ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…Later, in 2019, pathogenic variants involving the gene ZMIZ1 were identified in a cohort of 19 NEDDFSA cases from a transatlantic collaborative effort ( Carapito et al, 2019 ). In the same year of 2019, an affected father and his two sons were identified to be suffering from the ZMIZ1-related neurodevelopmental disorder in Florida ( Latchman et al, 2020 ). In 2021, Phetthong et al reported a 5-year-old Thai girl with developmental delay, facial phenotypes resembling Williams syndrome, and cardiac defects.…”
Section: Introductionmentioning
confidence: 99%